Robust concrete crack inspection using terrestrial laser scanning / Muhammad Ikhsan Irwanshyah - Irwanshyah, Muhammad Ikhsan (2018)
Crack is one of the reasons why the deformation survey must be done to the building facade. Inspections need to be done in order to reduce risks and determine whether the building safe to live in or use. There are many ways to measure the crack but in this research is focusing on measuring the crack using the terrestrial laser scanner. The conventional method had a few limitations to measure the crack. However, this research aims to investigate robust procedure to perform crack inspection on building facade. The data will be collected using different laser scanner resolutions to determine which resolution is enough to visual the crack. The crack can be determine based on the intensity value as the crack on the building facade will give a different intensity value when the laser point interact with the crack and return to the laser scanner in order to record the data. Result from this research are to produce the robust procedure for crack detection using terrestrial laser scanner. As the conclusion, the implementation of terrestrial laser scanner is useful and effective method in crack detection purpose.